2019
DOI: 10.22435/hsr.v21i4.752
|View full text |Cite
|
Sign up to set email alerts
|

Kebugaran Jasmani menurut instrument GPAQ dibandingkan dengan VO2max pada wanita umur 25 sampai 54 tahun

Abstract: The Global Physicall Activity Questionnaire (GPAQ) is the most commonly used tool for measuring physical activity in surveys. Receiver Operating Analysis (ROC) is performed to see the GPAQ instrumen's diagnostic ability to physical activity with VO2max as a comparison. The aims of study is to determine the distribution of METs minutes / weeks of each activity domain, cut off point METs, area under the curve (AUC), sensitivity, specificity, positive predictive value and negative predictive value of GPAQ instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The results of this study are in line with this said research, by obtaining a cut-off value of 3.8 for METs in predicting readmissions in ≤30 days. METs values obtained for women aged 25–54 years in Bogor, Indonesia, using the GPAQ tool mostly tends to over-estimate with an average METs value of 4.271 ± 2.874 [ 23 ]. Myers et al demonstrated that each 1 metabolic equivalent (METs) increase in functional capacity reduced 12% risk of death in cardiovascular patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with this said research, by obtaining a cut-off value of 3.8 for METs in predicting readmissions in ≤30 days. METs values obtained for women aged 25–54 years in Bogor, Indonesia, using the GPAQ tool mostly tends to over-estimate with an average METs value of 4.271 ± 2.874 [ 23 ]. Myers et al demonstrated that each 1 metabolic equivalent (METs) increase in functional capacity reduced 12% risk of death in cardiovascular patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physical fitness is categorized as average if the subject finishes the test for 6 minutes and has more than 116 pulses per minute. Physical fitness is categorized as weak if the subject cannot finish the test for 6 minutes (Nainggolan, Indrawati, and Pradono, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini berarti bahwa semua butir pernyataan dinyatakan valid. Alat ukur yang digunakan untuk mengukur aktivitas fisik pada penelitian ini yaitu Global Physical Activity Questionnaire, yang diadopsi dari World Health Organization (WHO) (Nainggolan, Indrawati, & Pradono, 2019).…”
Section: Instrumenunclassified